Synchrotron-based XPS studies of AlGaN and GaN surface chemistry and its relationship to ion sensor behaviour - Khir, F.L.M.; Myers, M.; Podolska, Anna; Sanders, T.M.; Baker, M.; Nener, B.; Parish, G. (Elsevier BV North-Holland, 2014)
Soft X-ray photoelectron spectroscopy was used to investigate the fundamental surface chemistry of both AlGaN and GaN surfaces in the context of understanding the behaviour of AlGaN/GaN heterostructures as chemical field-effect transistor (CHEMFET) ion sensors. AlGaN and GaN samples were subjected to different methods of oxide growth (native oxide and thermally grown oxide) and chemical treatment conditions. Our investigations indicate that the etching of the oxide layer is more pronounced with AlGaN compared to GaN. Also, we observed that chloride ions have a greater tendency to attach to the GaN surface relative to the AlGaN surface. Furthermore, chloride ions are comparatively more prevalent on surfaces treated with 5% HCl acid solution. The concentration of chloride ions is even higher on the HCl treated native oxide surface resulting in a very clear deconvolution of the Cl 2p1/2 and Cl 2p3/2 peaks. For GaN and AlGaN surfaces, a linear response (e.g. source-drain current) is typically seen with variation in pH of buffered solutions with constant reference electrode voltage at the surface gate; however, an inverted bath-tub type response (e.g. a maximum at neutral pH and lower values at pH values away from neutral) and a general tendency to negative charge selectivity has been also widely reported. We have shown that our XPS investigations are consistent with the different sensor response reported in the literature for these CHEMFET devices and may help to explain the differing response of these materials.